In memory of József Vörös mycologist (1929–1991) on the 25th anniversary of his death - Kövics, György (Acta Agraria Debreceniensis, 2017)
Twenty five years ago died professor József Vörös, internationally recognized mycologist, phytopathologist. On the field of microscopic fungi research, especially on taxonomy of plant pathological conidial fungi (Deuteromycetes, Coelomycetes, Hyphomycetes) gained imperishable reputation during his more than 40 years research activity. As author of 17 fungus taxa and publisher of numerous mycological data J. Vörös took place in the history of mycology.